Exoticism and Reception on the Silk Roads: Two Pieces of Roman Glass Found in Tombs of Ancient China (4th-6th Century A.D.) - Xiao, Yang (Sinología hispánica. China Studies Review, 2024)
In the ancient world, China wasn’t part of the traditional centers in the manufacture of glass, a material that was considered rare and luxurious by the ancient Chinese people. Nevertheless, in the sites there has been excavated a certain amount of glass vessels whose typical characteristics demonstrate their external origin both evidenced by typological analysis, decorative style and chemical composition. The study of ancient Chinese glass, however, has not received sufficient attention, existing researches on exotic glass mainly focus on aspects such as its foreign nature and routes of introduction, and lacks in-depth reflections on the roles of China or other ancient East Asian countries in the further transmission of glass, as well as a thorough consideration of the degree of reception of glass in another cultural environment. Therefore, in the context of the Silk Roads between the fourth and sixth centuries AD, this paper takes as an example the two pieces of glass found in the Feng House Necropolis in Jingxian (Hebei Province). By examining their characteristics, analyzing their chemical composition and comparing them with parallel specimens, it is clear that they are typical of the Roman Empire, both produced on the eastern coast of the Mediterranean area, and very possibly were introduced into China through the Steppe Routes and continued to radiate other parts of East Asia, such as the Korean peninsula. However, the introduction of glass in China, although limited in volume and without a profound impact on the recipient country, still left its mark on Buddhist practices and art.